2008
DOI: 10.2500/ajr.2008.22.3121
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Exenteration: A Dilemma in Mucormycosis Presented with Orbital Apex Syndrome

Abstract: The favorable outcome was attributable to rapid correction of the underlying medical condition; wide local excision and debridement of all involved and devitalized sinonasal and periorbital tissue, while establishing adequate sinus and orbital drainage; daily endoscopic assessment with multiple sinus debridement when necessary; daily irrigation of the involved areas; and high-dose i.v. amphotericin B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 26 publications
(71 reference statements)
2
30
0
1
Order By: Relevance
“…However, some reports have claimed successful treatment of rhino-orbital mucormycosis. 7,8,13,18,19 Reviewing our patients' causes of death revealed complications associated with extensive mucormycosis involvement and severe comorbidity. Of the former, CNS involvement can be considered a fatal complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some reports have claimed successful treatment of rhino-orbital mucormycosis. 7,8,13,18,19 Reviewing our patients' causes of death revealed complications associated with extensive mucormycosis involvement and severe comorbidity. Of the former, CNS involvement can be considered a fatal complication.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 However, following wide application of nasal endoscopy in sinus surgery, other authors have reported comparable results with frequent endoscopic debridement. 1,[11][12][13] These authors have claimed that, in selected cases, this method has less morbidity, a better surgical field of vision, and comparable results. 2,11,12 However, the poor state of most infected patients results in high mortality rates regardless of treatment type.…”
Section: Introductionmentioning
confidence: 99%
“…In a multi-center study, Kaya et al 20 used local amphotericin B irrigation together with different standard treatments in 4 patients, but all of those patients died. Songu et al 21 reported that in 3 cases that underwent debridement and local amphotericin B irrigation in addition to systemic treatment, spread of the fungal infection was successfully halted and none of the cases required exenteration. Konuk et al 22 reported 2 fatal cases that did not receive amphotericin B irrigation, whereas in a report of 2 non-fatal cases by Özay et al, 23 one patient received local irrigation and the other did not.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the development of both antimicrobial treatments and endoscopic sinus operation has contributed to the successful management of orbital apex syndrome by the combined therapy of antimicrobial drug and drainage by endoscopic sinus operation. 1718 Zuma 19 descirbed that ozone aeration could disinfect Pseudomonas aeruginosa . Similarly, drainage by endoscopic sinus operation combined with antibiotics was effective for our case.…”
Section: Discussionmentioning
confidence: 99%